Inventions and their commercial exploitation in academic institutions: Analysing determinants among academics - Teita Bijedić; Simone Chlosta; Arndt Werner (Institut für Mittelstandsforschung (IfM) Bonn, 2016)
Institutions of higher education are considered as an important source of innovation. Consequently, big efforts are made to facilitate technology transfer from academia into the market. However, technology transfer at German universities does not seem to live up to its full potential. We find for example that while 18,5% of our sample did in fact generate at least one invention, only 4,5% of the sample are engaged in commercialization activities. Therefore the vast majority of generated inventions remains unexploited. Based on this finding, we analyze how individual, career-related, and institutional factors affect the innovation and knowledge transfer activities of male and female academics. We show that Gender differences as well as career and human capital related factors (e.g. scope of employment, professional experience, and leadership position) affect such innovation transfer activities. While women generate fewer inventions than men, the fulltime employed researchers with a professional experience outside of academia and a leadership position lead to more inventions as well as partly higher exploitation activities. – – Der Wissenstransfer und die Verwertung marktfähiger Erfindungen aus der Hochschulforschung stellt eine bedeutende Innovationsquelle dar, die wirtschftspolitisch breite Unterstützung erfährt. Doch trotz vielfältiger Bemühungen, diesen Prozess zu unterstützen, bleibt ein großer Teil der Innovationen an Hochschulen ungenutzt. Die vorgestellte Untersuchung hat zum Ziel, Determinanten (individuelle, berufsbezogene und Umfeldfaktoren) der Innovationstätigkeit aus der Sicht der an deutschen Hochschulen tätigen Wissenschaftlerinnen und Wissenschaftler zu untersuchen. Ergebnisse zeigen, dass an deutschen Hochschulen vor allem vollzeitbeschäftigte Wissenschaftler, die multidisziplinäre oder angewandte Forschung betreiben und daneben noch einer Selbstständigkeit nachgehen, besonders häufig Erfindungen generieren. Frauen bleiben dabei nicht nur insgesamt, sondern auch innerhalb der einzelnen Fächerverbünde hinter ihren männlichen Kollegen zurück. Liegen die Erfindungen erst einmal vor, lassen sich für ihre Kommerzialisierung keine Geschlechterunterschiede finden. In dieser Phase der Innovationstätigkeit sind marktbezogen Praxiserfahrungen ausschlaggebend.
Keywords: O31; O34; J16; 330; academics; gender; innovation; inventions; commercial exploitation; institutional context